2020
DOI: 10.1038/s41467-020-20053-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal symptom dynamics of COVID-19 infection

Abstract: As the COVID-19 pandemic progresses, obtaining information on symptoms dynamics is of essence. Here, we extracted data from primary-care electronic health records and nationwide distributed surveys to assess the longitudinal dynamics of symptoms prior to and throughout SARS-CoV-2 infection. Information was available for 206,377 individuals, including 2471 positive cases. The two datasources were discordant, with survey data capturing most of the symptoms more sensitively. The most prevalent symptoms included f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
130
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(168 citation statements)
references
References 28 publications
24
130
4
2
Order By: Relevance
“…Our findings are in-line with other longitudinal studies of mild COVID-19 patients, that also found high variability in the clinical course of the disease, and long durations (weeks after infection) of fatigue, shortness of breath [26], and smell and taste changes [27,28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in-line with other longitudinal studies of mild COVID-19 patients, that also found high variability in the clinical course of the disease, and long durations (weeks after infection) of fatigue, shortness of breath [26], and smell and taste changes [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…In light of the limited data available for mild COVID-19 patients, especially in the long term [9,11,26,27], our study provides important inputs regarding the disease course over a six-month period in ambulatory patients. The careful phone follow-up interviews further contributed to our findings' reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of Covid-19 clinical manifestation is very wide, as it includes asymptomatic infection, mild upper respiratory tract symptoms, mild and severe pneumonia, acute respiratory distress syndrome, sepsis and septic shock, [ 2 ] but also myalgia, fatigue, sputum production, headache, hemoptysis, diarrhea, anosmia, and ageusia. Furthermore, as clinical data became available, potential cardiovascular, gastrointestinal, neurological, and cutaneous manifestations of the disease were described by scientific literature [ 3 ]. Despite the course of the disease is often mild and undistinguishable from a common flu, in a considerable number of cases Covid-19 infection may require hospitalization, and can lead to an acute respiratory distress syndrome (ARDS) and death [ 1 ] [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the virus has rapidly spread across the globe and caused more than 90 million proven infections and over 2 million deaths. Disease severity ranges from asymptomatic infection to symptoms like cough, fever, muscle pain, and diarrhea to severe courses of infection including pneumonia with severe respiratory distress and a high risk of death [3][4][5] . While the majority of infected individuals experience a mild course of disease, elderly or individuals with pre-existing conditions are at higher risk for severe courses of COVID-19 6 .…”
mentioning
confidence: 99%